The Difficult Task of Assessing and Interpreting Treatment Deterioration: An Evidence-Based Case Study - Bloch-Elkouby, Sarah; Eubanks, Catherine F.; Knopf, Lauren; Gorman, Bernard S.; Muran, J. Christopher (Frontiers in Psychology, 2019)
Objectives: Literature on outcome assessment suggests that 35% to 40% of patients in randomized control trials terminate treatment with unchanged or higher levels of symptomatology. The goal of the present study was to shed light on this phenomenon and the factors accounting for it using a single case study design that investigates the process and outcome of a treatment conducted within a non-randomized clinical trial comparing a cognitive behavioral and a brief relational treatment. Method: The condition of L., a Caucasian man undergoing cognitive-behavioral therapy in a large metropolitan research program, was classified as deteriorating using the Reliable Change Index for the Inventory of Interpersonal Problems (IIP) and the Symptom Checklist-90 (SCL-90). Therapeutic process and outcome were examined using quantitative and qualitative methods rated by several sources. Results: Analysis showed that the treatment was delivered skillfully and that despite initial difficulties, a strong alliance eventually developed between the patient and their therapist whose perspectives on the outcome of therapy nevertheless diverged. The patient’s satisfaction with treatment was high, and he believed his deterioration was caused by its termination. Discussion: Results suggest that the deterioration was not caused by a rough process or a faulty delivery of the therapy. Several explanations were discussed in the context of the literature. Keywords: deterioration, treatment failure, case study, outcome, process, patient satisfaction